The Impact of Total Deceleration Area and Fetal Growth on Neonatal Acidemia in Vacuum Extraction Deliveries - Gal Cohen; Dorit Ravid; Nagam Gnaiem; Hadar Gluska; Hanoch Schreiber; Noa Leybovitz Haleluya; Tal Biron-Shental; Michal Kovo; Ofer Markovitch (MDPI AG, 2023)
We aimed to investigate the correlation between total deceleration area (TDA), neonatal birthweight and neonatal acidemia in vacuum extractions (VEs). This is a retrospective study in a tertiary hospital, including VE performed due to non-reassuring fetal heart rate (NRFHR). Electronic fetal monitoring during the 120 min preceding delivery was interpreted by two obstetricians who were blinded to neonatal outcomes. TDA was calculated as the sum of the area under the curve for each deceleration. Neonatal birthweights were classified as low (<2500 g), normal (2500-3999 g) or macrosomic (>4000 g). A total of 85 VEs were analyzed. Multivariable linear regression, adjusted for gestational age, nulliparity and diabetes mellitus, revealed a negative correlation between TDA in the 60 min preceding delivery and umbilical cord pH. For every 10 K increase in TDA, the cord pH decreased by 0.02 (p = 0.038; 95%CI, −0.05-0.00). The use of the Ventouse-Mityvac cup was associated with a 0.08 decrease in cord pH as compared to the Kiwi OmniCup (95%CI, −0.16-0.00; p = 0.049). Low birthweights, compared to normal birthweights, were not associated with a change in cord pH. To conclude, a significant correlation was found between TDA during the 60 min preceding delivery and cord pH in VE performed due to NRFHR.